Soft Computing Techniques-based Digital Video Forensics for Fraud Medical Anomaly Detection - Nanda, Sunpreet Kaur; Ghai, Deepika; Ingole, P. V.; Pande, Sagar (Computer Assisted Methods in Engineering and Science; Vol 30 No 2 (2023), 2022)
The current pandemic situation has made it important for everyone to wear masks. Digital image forensics plays an important role in preventing medical fraud and in object detection. It is helpful in avoiding the high-risk situations related to the health and security of the individuals or the society, including getting the proper evidence for identifying the people who are not wearing masks. A smart system can be developed based on the proposed soft computing technique, which can be helpful to detect precisely and quickly whether a person wears a mask or not and whether he/she is carrying a gun. The proposed method gave 100% accurate results in videos used to test such situations. The system was able to precisely differentiate between those wearing a  mask and those not wearing a mask. It also effectively detects guns, which can be used in many applications where security plays an important role, such as the military, banks, etc.